Bead-On-Plate Welding on S235JR Steel by Underwater Local Dry Chamber Process - Rogalski Grzegorz; Łabanowski Jerzy; Fydrych Dariusz; Tomków Jacek (Polish Maritime Research)
The article presents the results of the effect of parameters of underwater local dry chamber welding on the properties of padding welds. The effect of heat input and the type of shielding gas on the structure and hardness of welds was established. the functions for estimating the maximum hardness of the heat affected zone have been also elaborated